Linguistic prejudice and discrimination in Brazilian Portuguese and beyond: suggestions and recommendations - O’neill, Paul; Massini-Cagliari, Gladis [UNESP] (University of Toronto Press, 2019)
In this article we make a distinction between the prejudice and discrimination towards (a) different languages and their speakers and (b) different non-stan-dard varieties of the same language and their speakers, and argue that while the discrimination and prejudice towards (a) have been denounced by international institutions and both national and international laws are in place to guarantee the rights of speakers of different languages, the same protection has not been afforded to speakers of non-standard varieties of a language. We examine a specific case of this type of linguistic prejudice in Brazil. We discuss the effectiveness of efforts of linguists to combat linguistic prejudice based on the principle of error correction (Labov 1982) and, drawing on work by Cameron (2012c) and Bourdieu (1986), suggest that linguistic prejudice cannot be disen-tangled from other types of prejudice and that linguists need to have a much deeper understanding of and engagement with the values attached to linguistic forms. We conclude with a number of suggestions and recommendations in order to effectively combat linguistic prejudice.
Keywords: barbarism: error correction; Brazil; civilisation; discrimination; language; prejudice